Intervention programs for the body image improvement in Elementary School children - León González, M. P.; González-Martí, I.; Contreras Jordán, O. R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
Problems arising from a negative body image lead to the development of educational programs that, through different contents, try to improve the school-aged-children’s body image.  The aim of this study was to analyze the characteristics and effects of the most recent programs for children of Elementary School, in order to know the most effective ones.  Twenty-one programs were analysed, whose most common contents are self-esteem, media literacy, healthy dieting and physical activity.  Most of these programmes are based on an interactive methodology and an etiological approach.  In general, some programmes are effective on the improvement of some risk factors, although it has been seen little effect on body dissatisfaction and behaviors or symptoms of eating disorder, both in post-test and follow-up.  Some limitations are the lack of a control group and a follow-up assessment.